Memanfaatkan Limbah Tahu Menjadi Produk Siap Jual - Wan Laura Hardilawati; Vera Nzly; Nestytie Apta Rahmi; Calvin Akira Zulkarnaen; Waldi Awala; Ghani Firja Anshari (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
Soybean (glycine max) is widely used as a food ingredient, especially foods that contain lots of high protein. Soybean seeds can also be used as a source of energy and protein. The creation of new products from processed soybean dregs (glycine max) or tofu dregs will be sold through the 4.0 marketing method, namely by using offline and online systems with the results utilizing soybean dregs (glycine max) or tofu dregs which are processed into rengginang and then using packaging design/packaging. attractive and do marketing using e-commerce.